Surveying cytotoxic chemotherapy use in small animal cancer treatment: insights into use and influencing factors in New Zealand - Northover S; Hill K; Cogger N; Isaksen K (Taylor and Francis Group on behalf of the New Zealand Veterinary Association, 2025)
Aim: To determine how frequently cytotoxic chemotherapy is administered in small animal practice to treat cancer and the reasons why clinics and clinicians do or do not offer and administer chemotherapy in New Zealand. Methods: A cross-sectional study involving veterinarians working in small and mixed animal practice was performed using an online questionnaire distributed via social media and email. The survey included closed and open-ended questions on respondent demographics, frequency of chemotherapy administration, medications used, cancers treated, and factors influencing administration. Fisher's exact tests were used to assess associations between variables, and content analysis was applied to open-ended responses. Results: Completed questionnaires were returned by 164 veterinarians working in New Zealand during the study period. Of the 164 respondents, 131 (80%) stated that they would probably or definitely discuss cytotoxic chemotherapy with clients as a potential treatment option for small animals with cancer. Within the 12-months preceding July 2023, 56 (34%) respondents had personally administered chemotherapy and 96 (58.5%) worked at clinics where it was administered: 5 (3%) administered it weekly, 6 (4%) at least monthly, 21 (12.8%) every 1–6 months, and 22 (13.4%) every 6–12 months. The most common reason given for administering chemotherapy was to provide comprehensive care to the patient. Improving quality and quantity of life was frequently reported. The most common reason for not administering chemotherapy was referral of cases externally for treatment. Excluding referral, respondents stated they do not administer chemotherapy because of insufficient knowledge regarding chemotherapy and the medications used, or insufficient training in how to handle and administer cytotoxic medications. Of the veterinarians that do not currently perform chemotherapy, 40% and 42% would consider performing it if they had additional education in oncology and chemotherapy, and in the handling and administration of cytotoxic medications, respectively. Conclusion: Cytotoxic chemotherapy is frequently discussed as a treatment option by veterinarians in New Zealand but is currently administered by a smaller proportion. Decisions to use chemotherapy are guided by quality-of-life considerations and adherence to standards of care, while limited knowledge and training hinders its use by other clinicians. Clinical relevance: Chemotherapy is administered less frequently in New Zealand than in the UK. Continuing education and the development of resources that further clinicians' knowledge regarding oncology, chemotherapy, and safe drug handling and administration are needed to support wider adoption in clinical practice.
Keywords: Cytotoxic chemotherapy; New Zealand; small animal; cancer; frequency